ANALISIS STRUKTURAL FUNGSIONALISME TERHADAP TINGGINYA ANGKA PERNIKAHAN DINI DI DESA WRINGINANOM KECAMATAN PONCOKUSUMO KABUPATEN MALANG - Nisa', Saskia Choirun; Zuchrufi, Sherlyna Elsania; Jousi, Mohammad; Rifqi, Muhammad Jazil (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2024)
AbstractIn Indonesia, the rate or early marriage is very high. This is caused by several things, one of which is the culture of young marriage in certain social circles. The aim of this research is to describe what is behind the high rate of child marriage by analyzing it using the AGIL concept (Adaptation, Goal Attainment, Integration, Latency) from Talcott's functionalist structural theory. Parsons stated that culture is the basic unit of action because culture has norms and values. To achieve them, people must follow the goals of the culture itself. The research used is field research, where data is obtained directly from the results of field research or at the research site. The results of this research show that 1). Early marriage is carried out by couples